PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MENGGUNAKAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) PADA PESERTA DIDIK KELAS II SDN 02 CUPAK TANGAH KOTA PADANG - Putri Ardelia, Abidah; Adrias, Adrias; Azmi Alwi, Nur; Chandra, Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted due to the low level of beginning reading skills among second-grade students at SDN 02 Cupak Tangah, Padang. Students experienced difficulties in recognizing letters, distinguishing similar letter forms, and reading simple words fluently. In addition, previous teaching practices were less varied and had not optimally supported students in mastering early reading skills. This research aimed to examine the improvement of beginning reading skills through the use of the Structural, Analytic, Synthetic (SAS) method. The study employed a Classroom Action Research (CAR) design conducted in two cycles. Data were collected through observation and tests. The results showed that the implementation of the SAS method improved learning planning, teacher and student activities, and students’ beginning reading skills. The average score increased from 75.10 in the first cycle to 90 in the second cycle, with classical completeness improving from 50% to 92.86%. Thus, the SAS method effectively enhanced students’ beginning reading abilities.